Effect of bamboo species and mulch materials on turmeric crop production and curcumin contents - Bhardwaj, D.R.; Kikon, Grace; Thakur, C.L.; Kumar, Naresh (Indian Journal of Agroforestry, 2020)
Agroforestry with bamboo considerably influences economic development. This system is especially important and significant for developing countries, like India. We examined the performance of turmeric as understory crop with nine treatments comprising of seven leaf mulches with FYM (farm yard manure) plus RDF (recommended doses of fertilizers); FYM and RDF and control under two bamboo species, viz., Dendrocalamus asper Â and Dendrocalamus hamiltonii and sole cropping in order to determine the type of mulch and growing conditions that would improve turmeric crop productivity. The results indicate that treatment T (Artemissia vulgaris + FYM + RDF) showed best results for most of the 2 growth and yield attributes of turmeric crop viz., plant height (150.9 cm), number of leaves per clump (11.2), leaf length (73.6 cm), leaf breadth (22.2 cm), weight of mother rhizome per plant (70.6 g), weight of primary fingers per plant (43.6 g), number of secondary fingers per plant (2.6), weight of secondary fingers per plant (7.1 g) and yield (12.48 ton ha-1). Sole cropping displayed better results for yield traits for turmeric when compared with D. asper and D. hamiltonii. Further, soil moisture content (%) reported higher value under D. hamiltonii. Light transmission ratio (%) recorded during the investigation period reduced by 40% under bamboo canopy.